2012
DOI: 10.1063/1.3670328
|View full text |Cite
|
Sign up to set email alerts
|

Optical feedback mechanisms in laser induced growth of carbon nanotube forests

Abstract: We study optical feedback mechanisms occurring during growth of multi-walled carbon nanotube forests on transparent substrates. Growth is realised via laser-induced chemical vapour deposition using iron nanoparticle catalysts. In situ Raman and reflection spectroscopy employed clearly distinguish three growth phases. In the initial seed phase, growth of carbon nanostructures increases the laser absorption and this feedback enables growth of radially orientated carbon nanotubes. Understanding the laser interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…76,77 On top of that, transparency of the substrate for certain wavelengths is another property that significantly influences the growth method that can be used. The most commonly used substrate is silicon, although fused silica, [76][77][78] graphite and grafoil, 79 and porous Al 2 O 3 membranes 80,81 were also used in combination with laser-assisted growth. Shi et al 82 synthesized suspended multiwall (650 C) as well as single-wall (770 C) nanotubes on inverse opal templates of silicon covered with a NiFe catalyst.…”
Section: A Catalyst and Substratementioning
confidence: 99%
See 1 more Smart Citation
“…76,77 On top of that, transparency of the substrate for certain wavelengths is another property that significantly influences the growth method that can be used. The most commonly used substrate is silicon, although fused silica, [76][77][78] graphite and grafoil, 79 and porous Al 2 O 3 membranes 80,81 were also used in combination with laser-assisted growth. Shi et al 82 synthesized suspended multiwall (650 C) as well as single-wall (770 C) nanotubes on inverse opal templates of silicon covered with a NiFe catalyst.…”
Section: A Catalyst and Substratementioning
confidence: 99%
“…In fact, the laser type and wavelength could influence the resulting growth. Apart from the most commonly used CO 2 lasers, a wide variety of different laser sources have been reported to grow CNT structures, such as Ar-ion lasers, 80,81,91,96 Nd:YAG lasers, 78,92,97 diode lasers, 76,[98][99][100] and Nd:YVO 4 lasers. 77,78,93,94 These reported laser sources all are CW lasers where the beam irradiates the substrate continuously for a certain duration.…”
Section: Laser Sourcementioning
confidence: 99%
“…In 2012, M. C. D. Bock et al reported the growth of multi-walled CNT forests on transparent substrates by laser-induced chemical vapor deposition using iron nanoparticle catalysts and the TEM of the cross-sectional samples of these structures confirmed that the CNTs in the entire structure were multi-layered with an average diameter of 5 nm [279]. Although electrochemical capacitors (EC) charged and discharged faster than batteries, they were still limited by low energy density and slow rate.…”
Section: Carbon Materialsmentioning
confidence: 99%
“…Most CNTs synthesized using LCVD are multiwalled [35], and by tailoring laser irradiance, catalyst, and chamber pressures SWCNTs have been achieved [36]- [39]. The effects of laser beam structure [40] and catalyst particles on CNT morphology [41], optical feedback mechanisms [42], and CNT evolution in the early stage [43] have been investigated. These investigations have demonstrated the advantages of LCVD, such as fast CNT growth rates, instant start and stop of synthesis, and minimum substrate and grown CNT damage.…”
Section: Introductionmentioning
confidence: 99%